Exploring the Moderating Role of Sharia Compliance on the Effect of ESG Score on Financial Performance - Abdul Azis Safii; Chahhoub Fatimazahra; Ria Septiani; Ahmad Sholihudin (Image : Jurnal Riset Manajemen, 2026)
This study examines the effect of Environmental, Social, and Governance (ESG) performance on corporate financial performance and investigates the moderating role of Sharia compliance in this relationship. The research focuses on non-financial companies listed on the Indonesia Stock Exchange (IDX) that have ESG scores provided by Morningstar Sustainalytics. This study employs panel regression analysis on a sample of 58 non-financial companies listed on the Indonesia Stock Exchange from 2021 to 2024. The results indicate that ESG performance has a statistically significant negative effect on corporate financial performance. These findings suggest that companies with higher ESG scores, as measured by the Sustainalytics risk-based framework, are associated with greater perceptions of ESG-related risks, and therefore lower financial performance. Furthermore, Sharia compliance does not moderate the relationship between ESG and financial performance. These results imply that although ESG practices and Sharia principles share ethical and sustainability-oriented foundations, they do not operate synergistically in enhancing firm financial performance within the Indonesian capital market context. The findings contribute to the ESG and Islamic finance literature by highlighting the importance of ESG measurement approaches and market context. The study also offers insights for investors, regulators, and corporate managers regarding the interpretation of ESG scores and the role of Sharia compliance in investment decision-making.